Study of electrical and magnetic properties of Sa, La and Pb doped Bi1-x-yDyxCyFe1-yTiyO3 perovskite ceramics - Rai, Radheshyam
Polycrystalline sample of Bi0.8Dy0.1Ca0.1Fe0.9Ti0.1O3 (where C=Ba (DB), La (DL) and Pb (DP)) was prepared by a high-temperature solid state reaction technique. For the understanding of the multiferroic property, the relation between the crystal structures, magnetic transition and ferroelectric transitions with increasing temperature have been analyzed. X-ray diffraction analysis of the powders suggests the formation of a single-phase material with tetragonal structure. Studies of dielectric properties of the compound, studied in a frequency range 10(4)-10(6) Hz at different temperatures (25-30 degrees C), exhibits two dielectric anomalies one at 225 degrees C and other around 375 degrees C (ferroelectric-paraelectric type transition). By using VSM technique, a significant change in the magnetic properties was observed in the Bi0.8Dy0.1C0.1Fe0.9Ti0.1O3 system with Pb doping, It was seen that coercive field H-c and remnant magnetization M-R increase with for Pb but for La and Ba it decreases. (C) 2013 Elsevier Ltd. All rights reserved.